PENGAMBILAN KEPUTUSAN INVESTASI DI KALANGAN GEN Z BERDASARKAN LITERASI KEUANGAN, HERDING BEHAVIOR, DAN LINGKUNGAN SOSIAL - Putri, Indah Amelia; Hudaya, Robith (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.12.TAHUN.2024, 2024)
Investment has become a crucial part of personal financial planning among Generation Z, especially with the ease of digital access. However, low financial literacy, social environmental influences, and herding behavior can affect investment decisions. This study aims to analyze the impact of these factors on the investment decisions of Generation Z in Mataram City. A quantitative causal approach was employed, targeting a population of 105,786 Gen Z individuals residing in Mataram. An online questionnaire was distributed to 162 respondents selected through purposive sampling. Data analysis was performed using SmartPLS 3 software and Structural Equation Modeling (SEM) techniques. The results indicate that financial literacy and social environment have a positive and significant effect on Gen Z’s investment decisions in Mataram City, while herding behavior does not influence their investment choices.